Resource Allocation in Edge Computing: A Game-Theoretic Perspective - Kumar S.; Gupta R.; Lakshmanan K. (My University, 2025)
Edge computing is a novel computing framework that offers decentralized computing power in order to reduce latency and save bandwidth. This technology is critical in the fast-evolving app market, where app vendors hire edge servers to serve their users. To compete with others, each app vendor wants to employ the edge servers in such a way that it costs the least. Therefore, all app vendors need a solution that minimizes the cost of hiring edge servers. This paper proposes an Edge Server Hiring game (ESHGame), a game-theoretical approach to the problem that formulates it as a potential game. We demonstrate in ESHGame that app vendors collectively achieve at least one pure Nash equilibrium (PNE). We also set an upper bound on the price of stability in this game. © 2022 IEEE.